Peran Mahasiswa dalam Pengelolaan Data Kearsipan dan Kualitas Pelayanan di Nagari Bukit Buai Tapan - Lestari, Anggia Ayu; Meditamar, Muhd. Odha; Anwar, Khairul (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
Data management is a very important thing to do especially in the era of digitization because archived data are important files that are very useful in an institution. The management of archives is a source of information concerning an activity that explains the rights and obligations that must be managed in an institution. This research activity aims to improve the management of archives in Nagari Bukit Buai Tapan Kab. The South Coast of West Sumatra by planning the work program and evaluating the work program. The method used in this study is a qualitative method with a Case study approach. The results of the study were obtained that during 48 days the implementation of the work program was carried out very well and gained appreciation from the community in Nagari Bukit Buai Tapan.